2021
DOI: 10.1111/1753-0407.13169
|View full text |Cite
|
Sign up to set email alerts
|

The performance of noninvasive indexes of adults in identification of nonalcoholic fatty liver disease in children

Abstract: Background: The aim of this study is to evaluate the performance of three existing prediction scores which are applicable to adults for identifying nonalcoholic fatty liver disease (NAFLD) in Chinese children. Methods: We used data from routine check-up based medical records of 1845 children to validate the performance of three existing scoring systems including the hepatic steatosis index (HSI), Zhejiang University index (ZJU index), and triglyceride-glucose index (TyG index) in detection of NAFLD in children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The comprehensive computer literature search from PubMed, MEDLINE, Web of Science, EMBASE and the Cochrane Library revealed 4722 articles, as shown in Figure 1 . Ultimately, 20 studies involving 165,725 participants were included [ 10 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The comprehensive computer literature search from PubMed, MEDLINE, Web of Science, EMBASE and the Cochrane Library revealed 4722 articles, as shown in Figure 1 . Ultimately, 20 studies involving 165,725 participants were included [ 10 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The detailed situation of the included studies is presented in Table 2 . The regions included China [ 10 , 21 , 22 , 23 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] (n = 14), Iran [ 35 , 36 ] (n = 2), Korea [ 37 , 38 , 39 ] (n = 3) and Japan [ 24 ] (n = 1). Two studies [ 21 , 30 ] included only children, and 12 studies included only adults.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the incidence of MAFLD also signi cantly increases with the increase in TyG [33,34]. In other studies, the AUCs of the TyG index to detect adult MAFLD were 0.714-0.782, with MAFLD diagnosed by ultrasound [19,[35][36][37][38][39]. A study showed that the AUC of TyG was larger than that of ALT, with the AUC of TyG at 0.9 (95%CI 0.84-0.94) in biopsy-proven MAFLD with 80% sensitivity and 92% speci city when the cut-off value was 8.38 [40].…”
Section: Discussionmentioning
confidence: 83%
“…TyG is also associated with cardiometabolic diseases and is a risk prognostic factor for stroke, diabetes mellitus, acute myocardial infarction, and acute coronary syndrome [15][16][17]. In addition, TyG may be a useful indicator of MAFLD not only in adults but also in children and the elderly [18][19][20]. Therefore, this study aimed to compare the ability of TG/HDL-C and TyG to distinguish MAFLD from healthy people and establish a better prediction model for MAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…With the increment of TyG, the incidence of MAFLD signi cantly increased (33,34). The AUCs of the TyG index demonstrated by some studies in detecting adult MAFLD were 0.714-0.782 and their MAFLD was diagnosed by ultrasound (19,(35)(36)(37)(38)(39). Two researches among them mentioned that the AUC of TyG was larger than ALT.Fedchuk L et al discovered that the AUC of TyG was up to 0.9 (95%CI 0.84-0.94) in biopsy-proven MAFLD with 80% sensitivity and 92% speci city when the cut-off value was 8.38 (40).…”
Section: Discussionmentioning
confidence: 99%